CD95/Fas promotes tumour growth - Chen, Lina (2010)
CD95 (also called Fas and APO-1) is a prototypical death receptor that regulates tissue homeostasis mainly in the immune system through induction of apoptosis 1-3. During cancer progression CD95 is frequently downregulated or cells are rendered apoptosis resistant 4,5 raising the possibility that loss of CD95 is part of a mechanism for tumour evasion. However, complete loss of CD95 is rarely seen in human cancers 4 and many cancer cells express large quantities of CD95 and are highly sensitive to CD95 mediated apoptosis in vitro. Furthermore, cancer patients frequently have elevated levels of the physiological ligand for CD95, CD95L 6. These data raise the intriguing possibility that CD95 could actually promote the growth of tumours through its nonapoptotic activities 7. Here we show that cancer cells in general, regardless of their CD95 apoptosis sensitivity, depend on constitutive activity of CD95, stimulated by cancer-produced CD95L, for optimal growth. Consistently, loss of CD95 in mouse models of ovarian cancer and liver cancer reduces cancer incidence as well as the size of the tumours. The tumorigenic activity of CD95 is mediated by a pathway involving JNK and c-Jun. These results demonstrate that CD95 plays a growth promoting role during tumorigenesis and suggest that efforts to inhibit its activity rather than to enhance its activation should be considered during cancer therapy.